Bermedia Sosial Prespektif Al-Qur’an: Aplikasi Hermeneutika Hassan Hanafi atas Q.S Al-Hujurat: 6-8 Dan 11-12 - As-Tsauri, Sofyan; Sulfa, Nafilah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This article is entitled "Using Social Media from an Al-Qur'an Perspective (Application of Hassan Hanafi's Hermeneutics to Q.S. Al-Hujurat: 6-8 and 11-12)", with the aim of exploring the meaning and ethical implications of the verses of the Al-Qur'an. Dealing with social media issues. The main focus of this article is on the interpretation of the verses Al-Hujurat: 6-8 and 11-12 by Hassan Hanafi, a prominent Muslim scholar. By carrying out Hassan Hanafi's hermeneutical approach to analyze how the concept of social media can be understood and applied in a contemporary context. This research identifies the ethical principles of communication and social interaction outlined by Hassan Hanafi in interpreting these verses. Through the library research research methodology, data was collected through analysis of the text of the Al-Qur'an, Hassan Hanafi's interpretation, and related literature. The results of this research show that using social media, according to Hassan Hanafi's perspective, involves a deep understanding of Islamic values, justice and tolerance in disseminating information.